Hunger or Procreation-Related Benefits? The Growing Population and Strain on Resources Among Refugees in The Ugandan Nakivale Refugee Settlement - Nsamba, Ahumedi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The increasing number of refugee settlements necessitates increased resources from national and international organizations to support the well-being of refugees. The Nakivale Refugee Settlement's Base camp has developed strategies to diversify income sources, such as having a large number of children to receive payments from aid organizations. This has led to population pressure within the camp, impacting the host community and national and international budgeting. A qualitative study using snowball sampling and focus group discussions found indirect factors like resource shortages, gender dynamics, and remittances from INGOs contributing to population pressure. Direct factors include rape, prostitution, malnutrition, poor access to reproductive health care, and integration with host communities. Failing to resolve the issue of giving birth for aid collection could worsen the suffering of refugees. Recommendations include educating refugees on the negative effects of large populations, providing family planning instructions, and providing adequate training to reduce unemployment rates.